Orthorhombic ZrO2 thin films via atomic layer deposition from tris(dimethylamino)cyclopentadienyl zirconium and water - Ali, Basit; Ghiyasi, Ramin; Pekkanen, Joona; Lastusaari, Mika; Karppinen, Maarit (Elsevier, 2026)
Different zirconium dioxide phases exhibit attractive functional properties, making them suitable for various applications. Among these, orthorhombic o-ZrO2 is of particular interest due to its distinctive ferroelectric behavior. However, synthesizing phase-pure o-ZrO2 thin films has remained challenging. Here, we demonstrate a robust water-based atomic layer deposition (ALD) process for o-ZrO2 thin films using tris(dimethylamino)cyclopentadienyl zirconium as the precursor. The films were characterized by grazing-incidence X-ray diffraction (GIXRD), X-ray reflectivity (XRR), ellipsometry, X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), and photoluminescence (PL) techniques. In the deposition temperature range of 225–250 °C, the process yielded nearly phase-pure o-ZrO2 films with a growth-per-cycle (GPC) of 0.5 Å/cycle, whereas above 275 °C, monoclinic m-ZrO2 films were obtained with GPC of 0.6 Å/cycle. Interestingly, longer relaxation times during deposition were found to affect the growth rate, which we tentatively attributed to changes in crystallization dynamics and stabilization of different orthorhombic space groups.